Geoelectrical Investigation Along Miri Coast, East Malaysia: Evaluate the Vulnerability of Coastal Aquifer - Mohan Viswanathan, Prasanna; Ramdzani, I.A.B.A.; Ramasamy, Nagarajan; Chidambaram, S.; Venkatramanan, S. (2019)
© Published under licence by IOP Publishing Ltd. The coastal zones are subject to rapid development with growing and conflicting demands on the natural resources, and often they are subject to irreversible degradation. Many coastal aquifers around the world are experiencing some level of salinity encroachment. The most common geophysical method used for the groundwater investigation is Geoelectrical method. In this study, a total of 15 vertical electrical sounding (VES) were carried out using Schlumberger electrode arrangement along Miri coast. The field data was interpreted by using curve matching techniques using IPI2Win software. 53% of the area is dominated by 'Q' type curve indicates decreasing resistivity with depth. The resistivity spatial maps and pseudo cross-sections reveal that the low-resistivity values were observed in the northern side of the study area due to the natural saline water intrusion in the deeper aquifer and anthropogenic influence in the shallow aquifer.